Masked red-emitting carbopyronine dyes with photosensitive 2-diazo-1-indanone caging group - Kolmakov, Kirill; Hell, Stefan (Photochemical & photobiological sciences, 2012)
Caged near-IR emitting fluorescent dyes are in high demand in optical microscopy but up to now were unavailable. We discovered that the combination of a carbopyronine dye core and a photosensitive 2-diazo-1-indanone residue leads to masked near-IR emitting fluorescent dyes. Illumination of these caged dyes with either UV or visible light (λ < 420 nm) efficiently generates fluorescent compounds with absorption and emission at 635 nm and 660 nm, respectively. A high-yielding synthetic route with attractive possibilities for further dye design is described in detail. Good photostability, high contrast, and a large fluorescence quantum yield after uncaging are the most important features of the new compounds for non-invasive imaging in high-resolution optical microscopy. For use in immunolabelling the caged dyes were decorated with a (hydrophilic) linker and an (activated) carboxyl group.
Gesehen am 29.10.2018